Preoperative Progressive Pneumoperitoneum Revisited - Elstner, Kristen E.; Moollan, Yusuf; Chen, Emily; Jacombs, Anita S. W.; Rodriguez-Acevedo, Omar; Ibrahim, Nabeel; Ho-Shon, Kevin; Magnussen, John; Read, John W. (Frontiers in Surgery, 2021)
The comparatively recent introduction of preoperative chemical component relaxation in complex ventral hernia surgery has changed the way in which these patients can be managed. This technique, using Botulinum Toxin A (BTA) or similar, injected preoperatively into the lateral oblique muscles, confers flaccid paralysis to those muscles, facilitating fascial closure at time of surgery. Compounding the benefits of BTA is preoperative progressive pneumoperitoneum (PPP), a longstanding but often underappreciated technique using incremental insufflation to stretch the contracted abdominal musculature. We present 39 complex ventral hernia patients managed with BTA and PPP and evaluate their outcomes. This was a prospective study assessing 39 patients between 2013 and 2021 with complex ventral hernia who underwent preoperative abdominal wall preparation with bilateral BTA and PPP. BTA was performed a minimum of 2 weeks prior to PPP catheter insertion. Pneumoperitoneum was instilled between 3 and 10 days pre-operatively. All patients underwent serial abdominopelvic CT scan imaging, and underwent laparoscopic or laparoscopic-assisted hernia repair with placement of intraperitoneal onlay mesh (IPOM). 17 (43.6%) females and 22 (56.4%) males with a mean BMI of 34.2 kg/m2(range 21.8-58.7 kg/m2) were included in this study. The mean transverse defect size was 16.1 cm (range 7-25 cm) with a mean loss of domain of 37.1% (range 12-67%). Non-contrast CT imaging demonstrated a mean length gain of the lateral abdominal wall after BTA of 3.2 cm/side (range 0.18-14.0 cm), which increased to 4.4 cm/side (range 0.23-13.4 cm) after PPP (p<<0.001). Twenty-three (60.5%) patients had 1 or more complication related to PPP, none requiring intervention. The combination of BTA and PPP have again shown to be useful adjuncts in the repair of complex ventral hernia. Each technique has their own distinct indications and advantages, but together they compliment each other immensely. This combination is particularly helpful in patients with multi-recurrent hernias, who have significant defect size and loss of domain. The addition of PPP facilitates re-establishment of abdominal visceral right of domain, as well as passively elongating the contracted abdominal musculature. PPP is not without possible complications, however, and the risks and benefits must be weighed up for each individual patient.